A new species of Paraclimenes from New Zealand waters (Crustacea: Decapoda: Palaemonidae) - Grave, Sammy De; Forman, Jeff (Zootaxa, 2025)
A new species of the palaemonid genus Paraclimenes is described from relatively deep water in New Zealand. The new species can easily be distinguished from the only other two known species in the genus by the non-spatulate chela of the first pereiopod, the size of the uropods and the produced distal telson margin.